Solar PV rural electrification and energy poverty: A review and conceptual framework with reference to Ghana - George Yaw Obeng; Hans-Dieter Evers (University of Bonn, Center for Development Research (ZEF), 2009)
In spite of the intention of governments to increase the use of renewable energy in electricity supply, particularly the use of solar photovoltaic (PV) for energy poverty reduction in rural and peri-urban areas of Africa, there is relatively little information on how solar PV electrification impacts on energy poverty reduction. Therefore, there is a gap in the literature and hence the need for continuous research. Using Ghana as a reference country, the historical trend, donor cooperation and other aspects of solar PV rural electrification are discussed . The paper illustrates the intersectoral linkages of solar PV electrification and indicators on education, health, information acquisition, agriculture and micro-enterprises. It also reviews sustainability related issues including costs and market barriers, subsidies, stakeholders involvement, political and policy implications, which are critical factors for sustainable market development of solar PV and other renewables. Finally, a common framework is developed to provide a basic understanding of how solar PV electrification impacts on energy-poverty. This framework provides a structure of the interrelated concepts and principles relevant to the issues under review.
urn:nbn:de:101:1-20090316233
Keywords: 330; Rural electrification; solar PV electrification; energy-poverty; Ghana; Africa